NARASI RELIGI DALAM FILM BOLLYWOOD (ANALISIS NARATIF DALAM FILM â€œPKâ€) HALAMAN JUDUL RELIGIOUS NARRATIVE IN BOLLYWOOD MOVIE (NARRATIVE ANALYSIS IN THE MOVIE â€œPKâ€ ) - Intan Permata Sari (ILKOM 16 UMY 171, 2016)
*171 Religious movies have been giving more variation on the recent Bollywood movies. One among others is the movie â€œPKâ€ which took religious diversity in India as its theme. This movie portays the differences on ordinances, cultures, and faith of various religions which are often not in accordance to each other and therefore become the big question in the movie of â€œPKâ€. This research used the thecnique of Algirdas Greimas narrative analysis model, by overviewing the structure adn element of narration.Greimas analogizes naration as a structure of meaning, as if a sentence consisting series of words with their respective position and function; as subject, object, predicate, and its structure. The reseacrh indicated that the movie of â€œPKâ€ displays God as a major focus behind every religious leader. This movie shows that religious leaders occasionally give false interpretation on religious teachings by providing misleading information for people and them away from the truth.